Brachial artery pseudo-aneurysm in intravenous drug abuser: a rare case report - Nabi, Naveed; Beigh, Firdous; Mir, Showkat (International Surgery Journal, 2019)
Brachial artery pseudo-aneurysm (BAP) is a rare entity because pseudo-aneurysms are common in lower limbs.1 Usual causes of BAP are humeral fractures, iatrogenic causes (repeated punctures for sample collection, following construction of Brachio-cephalic fistula) or some genetic causes like Ehler Danlos syndrome (EDS). This case has been reported to highlight the importance of considering all the differential diagnosis while evaluation of an upper limb swelling especially in the cubital fossa and due consideration of history of any IV drug abuse.